Italy's eighteenth century : gender and culture in the age of the grand tour - Findlen, Paula; Roworth, Wendy Wassyng, 1945-; Sama, Catherine M. (Stanford University Press, 2009)
This work illuminates the social and cultural landscape of 18th-century Italy by exploring how questions of gender in music, art, literature, science, and medicine shaped perceptions of Italy in the age of the Grand Tour.